2021
DOI: 10.1016/j.jmig.2020.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Treatment of Ureteral Endometriosis: A Systematic Review

Abstract: Objective: To review the literature for the preoperative clinical characteristics, surgical findings, and outcomes of patients who underwent laparoscopic surgical treatment of ureteral endometriosis (UE). Data Sources: A systematic search was performed in the PubMed and Scopus databases. Methods of Study Selection: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, studies in English language that assessed UE treated surgically by laparoscopy published between 2008 and 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…Symptoms in patients with UE are often atypical. Fernando et al concluded that after laparoscopic surgery for patients with UE in the past 10 years, dysmenorrhea (76.3%) and pelvic pain (59.6%) were the most common symptoms, and ureteral obstruction symptoms only accounted for 9.9% [ 4 ]. In a retrospective analysis of this case, the patient had dysmenor-rhea but ignored it because it could be tolerated, reminding clinicians that in cases of dysmenorrhea with hydronephrosis, patients should be alerted to the possibility of urinary tract endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms in patients with UE are often atypical. Fernando et al concluded that after laparoscopic surgery for patients with UE in the past 10 years, dysmenorrhea (76.3%) and pelvic pain (59.6%) were the most common symptoms, and ureteral obstruction symptoms only accounted for 9.9% [ 4 ]. In a retrospective analysis of this case, the patient had dysmenor-rhea but ignored it because it could be tolerated, reminding clinicians that in cases of dysmenorrhea with hydronephrosis, patients should be alerted to the possibility of urinary tract endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In these cases, developing the paravesical and pararectal spaces is necessary. [22][23][24] Consequently, the UA occlusion at the origin appears to be a safer and more reproducible maneuver to complete hysterectomy. 21 Moreover, we observed two (2.2%) cases of ureteral duplication in the OR group.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the failure to close UAs at the UL was significantly associated with the intraoperative identification of endometriosis and the need for parametrectomy and ureterolysis 21–23 . In these cases, developing the paravesical and pararectal spaces is necessary 22–24 . Consequently, the UA occlusion at the origin appears to be a safer and more reproducible maneuver to complete hysterectomy 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In such a setting, correctly predicting nonobstructive ureteral involvement may not change the outcome to a great extent, because the women are operated on by the best available surgeon in any case. In less specialized settings, the prediction of ureteral involvement may well be more relevant but, in our opinion, not so much to try to better plan the surgical team, but instead to refer the patient to centers of expertise with the objective of optimizing the efficacy of the procedure and minimizing the risk of complications, two variables that are strictly operator-dependent (1,2,5).…”
mentioning
confidence: 99%
“…This is a very useful safety maneuver, not only to identify extrinsic ureteral compression but also to prevent inadvertent and potentially unrecognized intraoperative iatrogenic ureteral lesions. However, not all gynecologists are trained to safely perform ureteral isolation and ureterolysis in women with severe deep endometriosis, even when the lesion sites and characteristics are correctly predicted preoperatively (5).…”
mentioning
confidence: 99%